Effects of Virtual Human Animation on Emotion Contagion in Simulated Inter-Personal Experiences - Yanxiang Wu; Babu, Sabarish V.; Armstrong, Rowan; Bertrand, Jeffrey W.; Jun Luo; Roy, Tania; Daily, Shaundra B.; Cairco Dukes, Lauren; Hodges, Larry F.; Fasolino, Tracy (IEEE transactions on visualization and computer graphics, 2014)
We empirically examined the impact of virtual human animation on the emotional responses of participants in a medical virtual reality system for education in the signs and symptoms of patient deterioration. Participants were presented with one of two virtual human conditions in a between-subjects experiment, static (non-animated) and dynamic (animated). Our objective measures included the use of psycho-physical Electro Dermal Activity (EDA) sensors, and subjective measures inspired by social psychology research included the Differential Emotions Survey (DES IV) and Positive and Negative Affect Survey (PANAS). We analyzed the quantitative and qualitative measures associated with participants' emotional state at four distinct time-steps in the simulated interpersonal experience as the virtual patient's medical condition deteriorated. Results suggest that participants in the dynamic condition with animations exhibited a higher sense of co-presence and greater emotional response as compared to participants in the static condition, corresponding to the deterioration in the medical condition of the virtual patient. Negative affect of participants in the dynamic condition increased at a higher rate than for participants in the static condition. The virtual human animations elicited a stronger response in negative emotions such as anguish, fear, and anger as the virtual patient's medical condition worsened.